The Effect of Reap (Read, Encode, Annotate, and Ponder) Technique on Students’ Reading Comprehension of Narrative Text At The Eighth Grade SMP N 1 Angkola Barat In 2021/2022 Academic Year - srimaharani tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2022)
The objectives of the research are: 1) to know the application of REAP (Read, Encode, Annotate, and Ponder) Technique on students’ reading comprehension of narrative text, 2) to know the students’ reading comprehension of narrative text before and after using REAP (Read, Encode, Annotate, and Ponder) technique, 3) to know whether there is any significant effect of REAP (Read, Encode, Annotate, and Ponder) technique on students’ reading comprehension at the Eighth grade of SMP N 1 Angkola Barat. This research uses experimental method. The population is all the Eighth grade students which are devided into six classes and total are 164 students. The samples are 28 students by using purposive sampling. The technique of collecting data is used questioner and test. The result of the research are, application of REAP technique is 76% categorized “Good”. The students’ reading comprehension of narrative text before using REAP technique is 26 categorized “Fail” and after is 79 categorized “Good”. The calculation of ttest formula is 29.82 and the ttable is 2.05 (ttest 29.82 > ttable 2.05). It means that there is any significant effect of REAP technique on students’ reading comprehension of narrative text at the Eighth grade of SMP N 1 Angkola Barat. Keywords: REAP Technique, Teachning, Method, Reading and Narrative Text Tujuan dari penelitian ini adalah: 1) untuk mengetahui sejauh mana Penerapan teknik REAP terhadap pemahaman siswa membaca teks naratif, 2) sejauh manakah pemahaman siswa membaca teks naratif sebelum dan sesudah menggunakan teknik REAP, 3) Apakah ada pengaruh yang signifikan dari teknik REAP terhadap pemahaman siswa membaca teks naratif di kelas VIII-B SMP N 1 Angkola Barat. Penelitian ini menggunakan metode eksperimental. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP N 1 Angkola Barat yang berjumlah 164 siswa. Sampel adalah VIII-B yang berjumlah 28 siswa yang diambil secara purposive sampling. Dalam pengumpulan data peneliti menggunakan lembar quetioner dan tes sebagai instrumen. Hasil dari penelitian ini adalah: 1) Penerapan teknik REAP adalah 76%, dengan kategori “Good”. 2) Nilai rata-rata pemahaman siswa membaca teks naratif adalah 26 dan dikategorikan “Gagal”. Sedangkan setelah menggunakan teknik REAP adalah 79, dikategorikan “Baik”. Hasil perhitungan ttest yaitu 29.82 dan ttabel yaitu 2.05. Ini berarti ada pengaruh yang signifikan dari teknin REAP terhadap pemahaman siswa membaca teks naratif dikelas VIII SMP N 1 Angkola Barat. Kata Kunci: Teknik REAP, Mengajar, Metode, Membaca, dan Teks Naratif